Post-2013 EU Common Agricultural Policy, Trade and Development - MATTHEWS, ALAN (International Centre for Trade and Sustainable Development (ICTSD), 2011)
The European Commission forwarded legislative proposals for reform of the Common Agricultural Policy (CAP) to the European Council and the European Parliament in October 2011. These proposals, which build on an earlier Communication of the Commission in November 2010, initiate the legislative procedure to agree the new regulations which may take up to 18 months to complete. Because of the scale of the EU as a major player in global agricultural markets, changes to its agricultural policy can potentially have repercussions for other countries. This paper analyses what the trade and development implications of the Commission?s proposals might be.
PUBLISHED
Keywords: Economics; Agriculture; Europe; CAP